Live-coding a machine learning model from scratch (O'Reilly Media, 2019)
"Do you want to build a machine learning model, but you aren't sure where to start? Starting with an empty notebook, Sara Robinson (Google) live-codes a simple neural network in TensorFlow. She then demonstrates how to train and serve the model on Google Cloud Platform and uses the deployed model to generate predictions from a web app. This session was recorded at the 2019 O'Reilly Open Source Software conference in Portland."--Resource description page